1997
DOI: 10.1016/s0035-9203(97)90401-6
|View full text |Cite
|
Sign up to set email alerts
|

Maloprim® malaria prophylaxis in children living in a holoendemic village in north-eastern Tanzania

Abstract: A randomized, double-'blind', placebo-controlled trial of weekly Maloprim (dapsone-pyrimethamine, D-P) for malaria prophylaxis was conducted at Magoda village in north-eastern Tanzania. The effect of D-P on the incidence of clinical malaria, Plasmodium falciparum prevalence and density, splenomegaly, and packed cell volume (PCV) was investigated in a cohort of 249 children (126 receiving D-P and 123 receiving placebo) aged 1-9 years. The case definition of clinical malaria (malaria fever) was measured axillary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…The villages were involved in malaria and filariasis studies as described elsewhere [38-40]. Currently, the two villages have a population of 2,934 individuals in 678 households and under-fives account for 13.2% of the entire population.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The villages were involved in malaria and filariasis studies as described elsewhere [38-40]. Currently, the two villages have a population of 2,934 individuals in 678 households and under-fives account for 13.2% of the entire population.…”
Section: Methodsmentioning
confidence: 99%
“…After an initial screening of parasite prevalence of the entire population of Magoda village in 1992, and based on the promising results from the Gambia [41], a Maloprim ® (3.125 mg pyrimethamine and 25 mg dapsone, GlaxoSmithKline, UK) trial was the first study to be implemented in Magoda in 1993–94 to test the prophylactic effects of weekly administration of the drug on parasite infections, anaemia and splenomegaly [40]. Children aged <10 years old were given either one or two tablet(s) of Maloprim ® to under-fives and those aged 5–9 years, respectively and followed-up weekly to determine their general condition and malaria infection status [40].…”
Section: Methodsmentioning
confidence: 99%
“…The area is holoendemic for malaria and has been described in detail elsewhere. 8 Study population. The present drug efficacy trial was carried out during the long rainy season in April 1996 at the beginning of a malaria transmission peak.…”
Section: Methodsmentioning
confidence: 99%
“…These studies their survival within their human host. In Kenya, studies of S. mansoni -infected persons have indicated that parasite-specific have also indicated that antigen-specific IgE and eosinophilia are associated with resistance to reinfection [2,3], implying IFN-g and IL-5 production is higher after clearance of infection [7]. Moreover, in Schistosoma haematobium -infected persons, that a bias toward Th2 might provide protection to invading parasites.…”
Section: Polymerase Chain Reactions a 648-bp Fragment Of The Dhfr Genementioning
confidence: 99%